Proses Berpikir Kreatif dalam Memecahkan Masalah pada Mahasiswa Jurusan Fisika FMIPA UNM - Kaharuddin Arafah; Mutahharah Hasyim; Ahmad Yani (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This research aims to describe the creative thinking process for students in solving problems related to physics problems in everyday life. This type of research is descriptive qualitative. The source of the data is students majoring in Physics in the physics education study program FMIPA Makassar State University semester 4 who have programmed Basic Physics courses. The results showed that there were differences in students' creative thinking processes in solving problems. This is based on the stages of the creative thinking process which include: (1) preparation; (2) incubation; (3) illumination; and (4) verification that experiences differences in time duration at the incubation and verification stages. The difference in students' creative thinking processes is also caused by the academic abilities possessed by each individual so that it has an impact in terms of solving problems.